A novel electrical rock typing approach to improve estimating formation resistivity factor in carbonate rocks - Milad Mohammadi; Mohammad Emami Niri; Abbas Bahroudi; Aboozar Soleymanzadeh; Shahin Kord (Journal of Petroleum Exploration and Production Technology)
Abstract Estimating petrophysical properties in carbonate rocks is challenging due to their complex pore structure, which leads to scattered data when analyzing the relationship between formation resistivity factor (F) and porosity. Traditional electrical rock typing methods showed limited success in reducing data scattering, as they primarily focused on the relationship between cementation factor and porosity. These methods often overlooked the importance of electrical quality in their analyses. In this study, the Electrical Zone Indicator (EZI) was introduced as a novel method that provides more accurate determination of reservoir electrical parameters compared to techniques like the Electrical Quality Index (EQI). EZI enhances EQI by minimizing its dependence on porosity that results in fewer and more precise electrical rock types. The method offers improved estimates of formation resistivity factor (F), cementation factor (m), and tortuosity factor (a). For instance, the cementation factor values for dataset 1 range from 1.685 to 3.33, and for dataset 2 from 2.108 to 3.268 values that align more closely with those expected in carbonate rocks. Data analysis confirms that EZI delivers highly accurate rock typing with determination coefficients (R²) greater 0.96. EZI enables a more comprehensive and accurate evaluation of reservoir rock types by providing more precise calculations of F and eliminating the need for data exclusion. In conclusion, the EZI method significantly improves the estimation of key reservoir parameters which makes it a valuable tool for petrophysical analysis in carbonate formations.